Integrated Urban Mobility for Our Health and the Climate: Recommended Approaches from an Interdisciplinary Consortium - Shilpa Dogra (MDPI AG, 2021)
Background: The purpose of this paper is to suggest an approach to aid with the creation of an interdisciplinary team and evidence-informed solutions addressing the urban mobility challenges facing many communities. Methods: We created a local Urban Mobility Consortium with experts from different disciplines to discuss the development of healthy, accessible communities, electrification, ride-sharing, and overarching issues related to urban mobility. A workshop and survey data collected during COVID-19 are presented in this paper. Results: Several evidence-informed recommendations are provided. Broadly, these were: (1) support the creation and development of accessible and safe active-transportation infrastructure; (2) incentivize and prioritize the use of active, public, and shared transportation over use of personal vehicles; (3) ensure connectivity of active transportation infrastructure with major destinations and public transportation options; (4) work towards electrification of personal and public transportation; and (5) work across siloes to improve integrated mobility to impact climate and health related outcomes, and enhance overall efficiency. Conclusions: An integrated approach is needed to improve mobility, access, and environmental impact. This needs to be carried out in the local context and requires government and non-governmental leadership.